Effects of selected dietary plant oils on survival, growth, fatty acid profile, and enzyme activity of a tropical hybrid carp (Barbonymus gonionotus ♀ × Hypsibarbus wetmorei ♂) larvae - Weerasingha, Rochana; Kamarudin, Mohd Salleh; Abd Karim, Murni Marlina; Ismail, Mohammad Fadhil Syukri (Elsevier, 2022)
Hybrid lemon fin barb is a new tropical carp species developed by crossing silver barb (Barbonymus gonionotus, ♀) with lemon fin barb (Hypsibarbus wetmorei, ♂) to cover the production gap in Malaysian aquaculture, as the tasty wild H. wetmorei is being overexploited. Different plant oils such as crude palm oil (CPO), linseed oil (LO), canola oil, sunflower seed oil and soybean oil were tested for the larval stage of this fast-growing and delicious carp species. Three-day old hybrid larvae were arbitrarily assigned to twenty 5-L tanks with a rate of 50 larvae L−1. After 20 days of the feeding trial, weight gain, total length gain and specific growth rate (SGR) of hybrid larvae fed diets containing CPO and LO were significantly higher (p < 0.05) than those of larvae fed with soybean oil. Survival of larvae fed CPO was significantly higher (p < 0.05) than those of larvae fed LO, canola oil and soybean oil diets. Total saturated fatty acids (SFAs) reported were high in hybrid larvae fed soybean oil followed by CPO while larvae fed CPO had the highest (p < 0.05) total body monounsaturated fatty acids (MUFAs). Total polyunsaturated fatty acids (PUFAs) of larvae fed CPO, LO, sunflower seed oil and soybean oil were significantly reduced (p < 0.05) accordingly. The larvae fed the CPO diet had the highest (p < 0.05) docosahexaenoic acid (DHA), arachidonic acid (ARA), total n-3 fatty acids and n-3/ n-6 ratio while dietary CPO and linseed oil increased larval body eicosapentaenoic acid (EPA) content. There was a significant interaction (p < 0.05) in dietary linoleic acid (LA) and ARA provided by different plant oils on ARA in hybrid larval body. Moreover, among plant oils used in the experiment, CPO was fetched at the lowest price. In conclusion, the use of dietary CPO in hybrid lemon fin barb larval diets is more economical and feasible.